2009
DOI: 10.1073/pnas.0801433106
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ1 promotes infection by human metapneumovirus

Abstract: Human metapneumovirus (hMPV) is a recently described paramyxovirus that causes lower respiratory infections in children and adults worldwide. The hMPV fusion (F) protein is a membrane-anchored glycoprotein and major protective antigen. All hMPV F protein sequences determined to date contain an Arg-Gly-Asp (RGD) sequence, suggesting that F engages RGD-binding integrins to mediate cell entry. The divalent cation chelator EDTA, which disrupts heterodimeric integrin interactions, inhibits infectivity of hMPV but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 61 publications
3
100
1
Order By: Relevance
“…Recently, Cseke et al (2009) provided evidence that integrin ␣v␤1 is a functional receptor for hMPV F protein (23). Consistent with this, the F proteins of all known hMPV strains contain a putative integrinbinding motif ( 329 RGD 331 ).…”
Section: H Uman Metapneumovirus (Hmpv) Is a Member Of The Genusmentioning
confidence: 62%
See 2 more Smart Citations
“…Recently, Cseke et al (2009) provided evidence that integrin ␣v␤1 is a functional receptor for hMPV F protein (23). Consistent with this, the F proteins of all known hMPV strains contain a putative integrinbinding motif ( 329 RGD 331 ).…”
Section: H Uman Metapneumovirus (Hmpv) Is a Member Of The Genusmentioning
confidence: 62%
“…Previously, it has been shown that hMPV engages ␣v␤1 integrin to mediate virus infection, suggesting that integrins might serve as functional receptors for hMPV (23). However, it is not known whether integrins are involved in hMPV F protein-mediated cell-cell fusion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to serving as a receptor for several RGD-containing matrix proteins (Hynes, 2002;Takada et al, 2007), V1 serves as a receptor or co-receptor for several viruses, including adenovirus (Davison et al, 2001;Li et al, 2001), foot-and-mouth disease virus (Jackson et al, 2002), parechovirus (Triantafilou et al, 2000) and metapneumovirus (Cseke et al, 2009). Although many integrins function as both adhesion and signaling receptors (Hynes, 2002;Takada et al, 2007), the role of V1 in cell signaling remains to be fully explored.…”
Section: Research Articlementioning
confidence: 99%
“…15 Little is known about the pathogenesis of HMPV, but an integrin alpha v beta 1 receptor has been identified that facilitates infection of the epithelial cells of the respiratory tract. 16 The most common reasons for hospitalization in children are bronchiolitis and pneumonia. Although HMPV has been associated with upper respiratory tract infections (rhinopharyngitis, laryngitis, croup), severe lower respiratory tract infection has been reported.…”
Section: Discussionmentioning
confidence: 99%